Determinants of Employee Work Motivation: Evidence from Compensation, Commitment, and Cooperation - Bayu Saputra Kurniawan; Zandra Dwanita Widodo; Sri Wijiastuti (ProBisnis : Jurnal Manajemen, 2026)
Human resources (HR) are a strategic asset that plays a vital role in determining organizational performance, including in government institutions such as the Sragen District Office, Sragen Regency. This study aims to analyze the influence of compensation, commitment, and cooperation on employee work motivation. A quantitative descriptive method was applied with a saturated sample of 35 employees selected from a total population of 70 employees. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and the coefficient of determination. The results show that compensation has a positive and significant effect on employee work motivation, indicating that adequate salaries and financial benefits increase employees’ enthusiasm and responsibility. Commitment also positively influences motivation, demonstrating that employees with strong loyalty and a sense of belonging are more motivated to achieve organizational goals. Cooperation similarly has a positive and significant effect, meaning that effective teamwork, communication, and shared responsibilities contribute to higher motivation levels. The coefficient of determination test shows that compensation, commitment, and cooperation collectively contribute 50.7% to employee work motivation, while the remaining 49.3% is influenced by other factors beyond this study, such as leadership style, job satisfaction, workload, and organizational culture. These findings emphasize the importance of strengthening compensation systems, organizational commitment, and team collaboration to enhance employee motivation and improve public service performance.